2015
DOI: 10.5152/eurasianjmed.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Doppler Findings in the Patients with Polyhydramnios before and after the Conservative Treatment

Abstract: Objective: The aim of this study was to evaluate the foetal renal blood flow with colour Doppler ultrasonography. Patients with polyhydramnios were investigated for the foetal renal artery pulsatility index (PI) at the beginning of the treatment, and after the conservative treatment in those who reached the normal amniotic fluid index. Materials and Methods:In this prospective study, 39 foetuses with polyhydramnios were evaluated at gestational weeks 26 to 36. The foetal development parameters, right and left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In the current study, resistance index (RI) and pulsatility index (PI) of renal artery is significantly higher in cases with isolated oligohydramnios compared to pregnant women with normal amount of amniotic fluid. The results of the current study were in accordance with the findings in the study of the studies done previously by Akdogan et al, [18]; Akin et al, [16] in which the Fetal renal artery pulsatility index (PI) ratio was greater than normal in oligohydramnios subjects and was statistically significant (p < 0.05). And Scottet al, [19] noted that renal artery pulsatility index ratios were greater than the standard amnion volume group in research conducted at 20 and 36 weeks of pregnancy in gestated women with oligohydramnios.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, resistance index (RI) and pulsatility index (PI) of renal artery is significantly higher in cases with isolated oligohydramnios compared to pregnant women with normal amount of amniotic fluid. The results of the current study were in accordance with the findings in the study of the studies done previously by Akdogan et al, [18]; Akin et al, [16] in which the Fetal renal artery pulsatility index (PI) ratio was greater than normal in oligohydramnios subjects and was statistically significant (p < 0.05). And Scottet al, [19] noted that renal artery pulsatility index ratios were greater than the standard amnion volume group in research conducted at 20 and 36 weeks of pregnancy in gestated women with oligohydramnios.…”
Section: Discussionsupporting
confidence: 93%
“…One of the studies demonstrated significant reduction in fetal RA RI and PI values in idiopathic polyhydramnios fetuses when compared to normohydramnios fetuses [24]. Akdogen et al evaluated fetal RA blood flow in polyhydramnios patients prior and after intervention showing a mild decrease in PI after intervention without any significant difference, which may be attributed to increased gestational age [26].…”
Section: Discussionmentioning
confidence: 99%
“…Akdogen et al. evaluated fetal RA blood flow in polyhydramnios patients prior and after intervention showing a mild decrease in PI after intervention without any significant difference, which may be attributed to increased gestational age [26].…”
Section: Discussionmentioning
confidence: 99%